Revision of the Habropoda and Tetralonioidella species of Taiwan with comments on their host-parasitoid relationships (Hymenoptera: Apoidea: Apidae) - Dubitzky, Andreas (Zootaxa, 2007)
The Taiwanese species of Habropoda and the corresponding cleptoparasite Tetralonioidella are revised and possible coevolution between these two genera is discussed considering their seasonal and altitudinal distribution patterns. An illustrated key to the Taiwanese species of both genera is provided. The following taxa of Habropoda and Tetralonioidella are described as new for science: Habropoda christineae sp. n., Habropoda sinensis taiwana ssp. n. and Tetralonioidella heinzi sp. n. Tetralonioidella himalayana formosana stat. n. is transferred to subspecific rank and a lectotype for Habropoda tainanicola tainanicola Strand, 1913 is designated. The female of Tetralonioidella hoozana Strand, 1914 is described for the first time.